Compliance of institutions in Manila to the accessibility law - Carlos, Ma. Charissa L.; Isaac, Cynthia V.; Muldong, Vanessa SM.; Navarro, Karen Ann A.; Ocheda, Thea Shiela O.; Villegas, Susan B.
Years after the enactment of the Accessibility Law, areas in Manila remain inaccessible to persons with disabilities despite continued efforts to enforce the law. The aim of this study was to determine the degree of compliance of public and private institutions in Manila to the specifications of the Accessibility Law with regard to ramps, parking areas, and washrooms and toilets. Visual inspection and measurement of accessibility features were conducted in institutions constructed/repaired/renovated between 1990 and 1999. A steel tape was used to measure these features and a checklist was adopted as a recording medium. Descriptive and inferential statistics were used to analyze the results. The results showed that both pubic and private institutions adhered to less than half of the specifications for each feature. Compliance to the Accessibility Law was generally minimal. This suggests that there is a need to strengthen implementation of the law. It further suggests a potential area for consultancy and advocacy for occupational therapists.
Keywords: Structural design; Access; Public standards